Dental bio-aerosol: a silent threat in dental practice - Arief Ichwan, Solachuddin Jauhari (2018)
Many dental procedures produce extensive bio-aerosols and splatter that are routinely contaminated with bacteria, viruses, and blood. Dental bio-aerosol has been considered as a potential occupational hazard in dental setting since the aerosolized microorganism from a patient’s mouth during dental treatment procedures may stay airborne for long periods of time and inhaled into the lungs of dental health care workers (DHCW). Reducing the risk of exposure to dental bio-aerosol has become a challenge for DHCW. To date, various infection control reports and procedures have been published to inform and educate dental health care personnel about the importance of practicing adequate infection control. This brief review highlights the potential risks that can be encountered with dental bio-aerosol. Various methods undertaken to control the infection caused by the aerosol are also discussed.